Kinetic-mechanistic Study of Periodate Oxidation of p-Chloroaniline - Kaushik, R.D.; P. Singh, Raghvendra (Asian Journal of Chemistry, 2010)
The kinetic-mechanistic studies related to the periodate oxidation of p-chloroaniline in acetone-water medium have been reported. The studies were made by employing the spectrophotometric technique. The order with respect to both oxidant and substrate has been found to be one in each. The rate increases on increasing the ionic strength and decreases with decrease in dielectric constant. The rate-pH profile has been discussed. The effect of free radical scavengers rejects the possibility of a free radical mechanism. The thermodynamic parameters have been evaluated and discussed. The main product of oxidation characterized by melting point and UV-VIS and IR and NMR spectrum was 4-chloro-1,2-benzoquinone. A suitable mechanism has been proposed and the rate law derived. 1 mol of the substrate was found to react with 2 moles of the oxidant.